Characteristics of Atheist Pre-Service Elementary Teachers. (13th November 2015) - Anderson, Derek
The purpose of this study was to investigate the beliefs and self-identities of 15 nonreligious pre-service elementary teachers (PSTs), as well as the role their lack of faith plays in their teaching. Semi-structured interviews and participant self-analyses served as data sources, which were used to categorize the PSTs into Silver's (2013 ) typology of nonbelief. Notably different from the distribution of Silver's national sample of nonbelievers, the nonreligious PSTs were much less engaged in their nonbelief and were more willing to comply with religious activities. The nonreligious PSTs were drawn to teaching due to their love of learning, and they intend to promote critical thinking and tolerance in their classrooms; however, 13 (87%) wof the PSTs expressed concern about the negative impact their lack of religion might have on their careers and intend to keep their lack of belief private.